Trajectories of long-term exposure to PCB153 and Benzo[a]pyrene (BaP) air pollution and risk of breast cancer - Pauline Desnavailles; Delphine Praud; Blandine Le Provost; Hidetaka Kobayashi; Floriane Deygas; Amina Amadou; Thomas Coudon; Lény Grassot; Elodie Faure; Florian Couvidat; Gianluca Severi; Francesca Romana Mancini; et al. (BMC, 2024)
Abstract Background While genetic, hormonal, and lifestyle factors partially elucidate the incidence of breast cancer, emerging research has underscored the potential contribution of air pollution. Polychlorinated biphenyls (PCBs) and benzo[a]pyrene (BaP) are of particular concern due to endocrine-disrupting properties and their carcinogenetic effect. Objective To identify distinct long term trajectories of exposure to PCB153 and BaP, and estimate their associations with breast cancer risk. Methods We used data from the XENAIR case-control study, nested within the ongoing prospective French E3N cohort which enrolled 98,995 women aged 40-65 years in 1990-1991. Cases were incident cases of primary invasive breast cancer diagnosed from cohort entry to 2011. Controls were randomly selected by incidence density sampling, and individually matched to cases on delay since cohort entry, and date, age, department of residence, and menopausal status at cohort entry. Annual mean outdoor PCB153 and BaP concentrations at residential addresses from 1990 to 2011 were estimated using the CHIMERE chemistry-transport model. Latent class mixed models were used to identify profiles of exposure trajectories from cohort entry to the index date, and conditional logistic regression to estimate their association with the odds of breast cancer. Results 5058 cases and 5059 controls contributed to the analysis. Five profiles of trajectories of PCB153 exposure were identified. The class with the highest PCB153 concentrations had a 69% increased odds of breast cancer compared to the class with the lowest concentrations (95% CI 1.08, 2.64), after adjustment for education and matching factors. The association between identified BaP trajectories and breast cancer was weaker and suffered from large CI. Conclusions Our results support an association between long term exposure to PCB153 and the risk of breast cancer, and encourage further studies to account for lifetime exposure to persistent organic pollutants.